Façade modules for eco-efficient refurbishment of buildings : glazing thermal performance to Guimarães climate - Sacht, Helenice Maria (2011)
During the last decades façade technologies have undergone to substantial innovations by integrating specific elements to adapt the mediation of the outside conditions to user requirements. This work reports the results of an ongoing investigation on a new façade system concept called "Façade Modules for Eco-Efficient Refurbishment of Buildings" and initially developed for Portugal. In this phase glazing modules made of high performance glasses were studied. Some results of thermal performance simulation for the Portuguese Guimarães city climate will be presented considering the use of three types of glazing modules and analyzing the influence of some parameters in heating and cooling energy needs for one room (size 25m²). Computational simulation was done with the Design Builder software considering the following parameters: three different double glazing types; two envelope types and four solar orientations. The results were obtained for heating and cooling energy needs and were compared to all glazing types. It can be noted a better performance to glazing compositions that combines solar control and self-cleaning glass with extra clear glass. The results indicated a decrease of heating energy needs by the use of self-cleaning glass and clear float glass. Additionally cooling energy needs decrease was observed by the use of a green solar control glass with low-e glass.